2003
DOI: 10.1128/mcb.23.20.7163-7176.2003
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Receptor RNA Activator Stimulates Proliferation as Well as Apoptosis In Vivo

Abstract: Steroid receptor RNA activator (SRA) is an RNA that coactivates steroid hormone receptor-mediated transcription in vitro. Its expression is strongly up-regulated in many human tumors of the breast, uterus, and ovary, suggesting a potential role in pathogenesis. To assess SRA function in vivo, a transgenic-mouse model was generated to enable robust human SRA expression by using the transcriptional activity of the mouse mammary tumor virus long terminal repeat. Transgenic SRA was expressed in the nuclei of lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(139 citation statements)
references
References 43 publications
6
132
1
Order By: Relevance
“…It has been reported that therapeutic administration of CD34 + cells has been shown to improve LVEF after experimental myocardial infarction . SRA1 is also known to stimulate proliferation as well as apoptosis in vivo (Lanz et al 2003). Taken together, all three genes appear to be important for cell proliferation or act as cell survival mediators and provide a novel mechanism contributing to heart failure.…”
Section: Three Cosegregating Genes Determine Dcmmentioning
confidence: 99%
“…It has been reported that therapeutic administration of CD34 + cells has been shown to improve LVEF after experimental myocardial infarction . SRA1 is also known to stimulate proliferation as well as apoptosis in vivo (Lanz et al 2003). Taken together, all three genes appear to be important for cell proliferation or act as cell survival mediators and provide a novel mechanism contributing to heart failure.…”
Section: Three Cosegregating Genes Determine Dcmmentioning
confidence: 99%
“…In vivo experiments showed that a decrease in SRA expression lead to a phenotype of myocardial contractile dysfunction in a zebrafish model [6], whereas an increase in mouse mammary gland stimulated proliferation and apoptosis [7]. Altogether, SRA is suspected to participate in normal and pathological events such as tissue differentiation and tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies have investigated the mechanisms of action of this functional RNA [2][3][4][5][6][7][8]. Through its core sequence (corresponding to exons 2-3-4 and part of exon 5), SRA behaves as a scaffold molecule that physically interacts with a number of RNA binding proteins and transcription factors via specific and critical secondary RNA structures [1][2][3][4]9].…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many studies have investigated the mechanisms of action of this functional RNA [2][3][4][5][6][7][8]. Through its core sequence (corresponding to exons 2-3-4 and part of exon 5), SRA behaves as a scaffold molecule that physically interacts with a number of RNA binding proteins and transcription factors via specific and critical secondary RNA structures [1][2][3][4]9]. These SRA-containing complexes involve a wide range of molecules including, but not limited to, multiple nuclear receptors, nuclear receptor co-regulators, and proteins involved in gene silencing and gene insulation [2,3,8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation